Penyuluhan Hukum tentang Urgensi Perlindungan Konsumen di Masa Covid-19 di SMAN 1 Palu - Asri Lasatu; Manga' Patila; Irzha Friskanov. S (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Consumers and business actors are the main actors in the process of transacting goods and / or services. In addition to consumers and business actors, the Government acts as a regulator in regulating the pattern of legal relations. This service activity is carried out to be able to increase students' knowledge and understanding of consumer law protection. By using the lecture and discussion method with the target students at SMAN 1 Palu. The conclusion is the lack of information and socialization of students regarding consumers and their protection. For the students, they only know the purchase of goods without realizing that every thing used must be protected. Especially if there are goods that are not suitable even to the detriment of consumers.